Two Recovered COVID-19 Cases Testing Positive Again for SARS-CoV-2 After Discharge in Hanoi, Vietnam - Thach, Pham Ngoc; Anh, Nguyen Tuan; Hang, Nguyen Viet; Duyet, Le Van (Archives of Clinical and Medical Case Reports, 2020)
Vietnam has successfully controlled the first waves of SARS-CoV-2 and has seen no community transmission since 15 April. One of the keys to this success is consistent quarantine of individuals who have been in contact with suspected cases or who are entering Vietnam from an endemic country. Reliable diagnostics to end isolation of patients and quarantine of individuals at risk are an essential component of this strategy. In this study we report two cases of who were discharged after testing negative twice for SARS-CoV-2 and then tested positive again. These are the first cases of virological relapse detected in Vietnam.